Balanceamento de linha de montagem com o uso de heurística e simulação: estudo de caso na linha branca - Farnes, Vanessa Carolina Fernandes; Pereira, Néocles Alves (Revista Gestão da Produção Operações e Sistemas, 2007)
A proper dimensioning of the production capacity is essential for the positioning of an enterprise in a globalized market. In enterprises with assembly line production, the dimensioning for the capacity is obtained by means of the balancing of the operations, by task assignment to the work stations, so that a performance measurement, such as the time, can be optimized. The line balancing methods considered in this paper correspond to a solution developed in an enterprise, a solution simply named as Balancer, and a heuristic tool named “Positional Weight”. In addition, a probabilistic simulation tool was used in order to verify and analyze the heuristic solution. Keywords: Line balancing, Capacity dimensioning, Positional weight, Simulation.